Potential association of nicotinamide on the telomerase activity and telomere length mediated by PARP-1 mechanism in myeloid cancer - Nur Rasyidah Muhammad; Azlina Ahmad; Siti Norasikin Mohd Nafi; Farizan Ahmad; Zariyantey Abdul Hamid; Sarina Sulong (Penerbit Universiti Kebangsaan Malaysia, 2020)
Administration of nicotinamide is affecting various types of cells through its survival, maturation, and differentiation. Nicotinamide as part of vitamin B3, plays an important role in DNA repair and maintenance of the genomic stability which related to its function as a NAD+ precursor that involve in many biological processes. During DNA breaks, PARP-1 mechanism will be activated and use NAD+ as a substrate in process of DNA damage and repair that will result to either cell repair and cell death. In the meantime, in presence of nicotinamide that is also acting as a PARP-1 inhibitor, causing inability of the repair mechanism to fix the entire DNA damage which also lead to the cell death. Therefore, loss of PARP-1 enzyme will cause disturbance in the DNA repair process. Telomere shortening rate was reduced in the presence of nicotinamide that might related with telomerase enzyme which able to maintain the telomere length of the cell. Other than that, telomere also can be influenced by PARP-1 activity where it might show some correlation between nicotinamide, telomere and telomerase that could related with PARP-1 mechanism. Currently, there is no treatment options that respond effectively in chronic myeloid leukemia (CML) in blast crisis (BC) phase without any side effect and it is require an identification of new drug therapies to treat the CML patients. By understanding the role and potential of nicotinamide relation with PARP-1 mechanism in telomere and telomerase status may improve the therapeutic strategy for chronic myeloid leukemia.